2015
DOI: 10.1007/s12274-015-0859-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled V2O5 interconnected microspheres produced in a fish-water electrolyte medium as a high-performance lithium-ion-battery cathode

Abstract: Interconnected microspheres of V 2 O 5 composed of ultra-long nanobelts are synthesized in an environmental friendly way by adopting a conventional anodization process combined with annealing. The synthesis process is simple and low-cost because it does not require any additional chemicals or reagents. Commercial fish-water is used as an electrolyte medium to anodize vanadium foil for the first time. Electron microscopy investigation reveals that each belt consists of numerous nanofibers with free space betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…For example, Wang et al reported the ESD synthesis of the 3D porous α‐phase V 2 O 5 thin film, the specific capacity of which decreases from 235 to 140 mAh g −1 in only 50 cycles . Among numerous reported V 2 O 5 and V 2 O 5 ‐based composite electrodes, only a few have shown a stable cycling performance with a capacity fading per cycle under 0.1% for two lithium insertion/extraction . Figure f demonstrates the cycling performance comparison of γ‐LiV 2 O 5 ‐ESD and γ‐LiV 2 O 5 ‐CEP at 0.5 C‐rate.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wang et al reported the ESD synthesis of the 3D porous α‐phase V 2 O 5 thin film, the specific capacity of which decreases from 235 to 140 mAh g −1 in only 50 cycles . Among numerous reported V 2 O 5 and V 2 O 5 ‐based composite electrodes, only a few have shown a stable cycling performance with a capacity fading per cycle under 0.1% for two lithium insertion/extraction . Figure f demonstrates the cycling performance comparison of γ‐LiV 2 O 5 ‐ESD and γ‐LiV 2 O 5 ‐CEP at 0.5 C‐rate.…”
Section: Resultsmentioning
confidence: 99%
“…In the first cycle, the reduction peak at 3.4 V corresponds to a phase change from α-V2O5 to ε-Li0.5V2O5; and peaks at 3.1 V and 2.3 V are assigned to the formation of δ-LiV2O5 and ɤ-Li2V2O5, respectively. [19][20][21][22] In the delithiation process, three anodic peaks at 2.5, 3.3 and 3.5 V are revealed, and they are ascribed to the corresponding reversed phase transformations from ɤ-Li2V2O5 to δ-LiV2O5, ε-Li0.5V2O5, and α-V2O5, respectively [35] . The CV curves for the 2 nd and 5 th cycles resembled that of the 1 st cycle suggesting an excellent reversibility of the cycling process.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] The capacity of the V2O5/3DC-CFs composite electrode in this voltage region is also apparently higher than those of the V2O5 nanostructure electrodes reported in the literature. [21][22][23][24][25][26][27] The cathode material of high-voltage plateau is necessary for increasing the operating voltage of lithium-ion batteries and, subsequently, enhancing the energy density. To have a fair comparison with the results reported previously, the capacities reported below in this work are, however, the total capacities measured for the voltage range from 4.0 to 2.0 V.…”
Section: Resultsmentioning
confidence: 99%
“…[87] To make up for these disadvantages, scientists came up with great new ideas that construct hierarchical 3D architectures assembled by low-dimensional nanomaterials. The micro-nano secondary architectures not only inherit the original properties of individual units but also derive the comprehensive advantages [89][90][91]. For instance, 3D V 2 O 5 nanospheres consisted of regularly arranged 2D nanosheets were fabricated via a hydrothermal method (Fig.…”
Section: Omentioning
confidence: 99%